Optic Neuropathy Secondary to Linezolid for Multidrug-resistant Mycobacterial Spinal Tuberculosis. (February 2015) - Agrawal, Rupesh; Addison, Peter; Saihan, Zubin; Pefkianaki, Maria; Pavesio, Carlos
Abstract Aim: To report a case of optic neuropathy secondary to Linezolid, second line anti tuberculosis agent. Case Report: 22 year Indian male with multidrug resistant spinal tuberculosis and TB meningitis was started on second line anti tuberculosis drugs. Within one month of onset of second line anti TB drug, he was noted to have optic neuropathy in both eyes. Visual field and electro diagnostics suggested optic neuropathy. Discussion: Linezolid is a synthetic oxazolidinone broad spectrum antibiotic and has been in off label use for multidrug resistant tuberculosis (MDR-TB). There are very scattered case reports of optic neuropathy secondary to use of this off label drug. In our case, the optic neuropathy was however reversible on stoppage of the drug. Conclusion: It seems prudent that baseline ophthalmological evaluation to be done for all patients to be subjected for treatment with this drug for any short term or long term therapy.